Trust-Based Secure Routing in Mobile Ad Hoc Network Using Hybrid Optimization Algorithm - Mukhedkar, Moresh Madhukar; Kolekar, Uttam (Computer journal, 2019)
Routing in mobile ad hoc networks (MANETs) is a hectic challenge due to the dynamic nature of the network. The provisional communication links are assured due to the infrastructure-independent capability of MANET, but with no proper centralized monitoring process, which makes routing in MANETs with respect to the security and trust a major issue. Thus, the paper introduces Advanced Encryption Standard-enabled Trust-based Secure Routing protocol based on the proposed Dolphin Cat Optimizer (AES-TDCO), which is an energy and trust-aware routing protocol. The proposed Dolphin Cat Optimizer is engaged in the optimal route selection based on the modeled objective function based on the trust factors, recent trust, historical trust, direct and indirect trust in addition to delay, distance and link lifetime. The Dolphin Cat Optimizer is the integration of Dolphin Echolocation and Cat Swarm Optimization algorithm that inherits the faster global convergence. The simulation using 75 nodes revealed that the proposed routing protocol acquired the maximal throughput, minimal delay, minimal packet drop and detection rate of 0.6531, 0.0107, 0.3267 and 0.9898 in the absence of network attacks and 0.7693, 0.0112, 0.3605 and 0.9961 in the presence of the network attacks.